On the impact of sample size on median lethal concentration estimation in acute fish toxicity testing: Is n = 7/group enough?. (31st March 2018) - Carr, Gregory J.; Bailer, A. John; Rawlings, Jane M.; Belanger, Scott E.
Abstract: The fish acute toxicity test method is foundational to aquatic toxicity testing strategies, yet the literature lacks a concise sample size assessment. Although various sources address sample size, historical precedent seems to play a larger role than objective measures. We present a novel and comprehensive quantification of the effect of sample size on estimation of the median lethal concentration (LC50), covering a wide range of scenarios. The results put into perspective the practical differences across a range of sample sizes, from n = 5/concentration up to n = 23/concentration. We also provide a framework for setting sample size guidance illustrating ways to quantify the performance of LC50 estimation, which can be used to set sample size guidance given reasonably difficult (or worst‐case) scenarios. There is a clear benefit to larger sample size studies: they reduce error in the determination of LC50s, and lead to more robust safe environmental concentration determinations, particularly in cases likely to be called worst‐case (shallow slope and true LC50 near the edges of the concentration range). Given that the use of well‐justified sample sizes is crucial to reducing uncertainty in toxicity estimates, these results lead us to recommend a reconsideration of the current de minimis 7/concentration sample size for critical studies (e.g., studies needed for a chemical registration, which are being tested for the first time, or involving difficult test substances). Environ Toxicol Chem 2018;37:1565–1578. © 2018 SETAC